Effects of seed priming on mucuna bracteata Dc. Ex Kurz seeds - Nurfariza, Aman (Universiti Malaysia Sarawak (UNIMAS), 2010)
A study was conducted to asses the effect of priming on Mucuna bracteata seeds which aimed to enhance vigorousity, germination and unifonnity in emergence of the seeds. The hardseeded coat ofM bracteata seed inhibited water and oxygen penetration to get through seeds and hence contributing to poor germination. Seeds were primed with four different priming techniques: hydropriming (soaking seeds in distilled water); ascorbate priming (primed within 1, 2, 3, 4 and 5% of ascorbic acid) and ethanol priming (primed using 1, 2 and 3% of ethanol concentration) for 0, 6, 12, 18, 24, 30 and 36 hours of priming period, respectively. In sulphuric acid priming, seeds were primed in 45, 55, 65 and 75% acid concentration for 0.0, 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 minutes. Significant difference within different solvent concentration and priming duration of ascorbate-, ethanol-and sulphuric acid-priming was observed effectively enhancing seed gennination except for hydropriming. However, there were no correlations between those two factors which improve gennination percentage. The highest germination was obtained with ascorbate priming at 1 % ascorbic concentration for 12 hours (M=99%) compared to others at 1% of ethanol concentration at 24 hours (M=95), a 24 hours of hydropriming (M=76) and 55% of sulphuric acid concentration at 1.5 minutes (M=89). Germination percentage was correlated with moisture content at comparable concentration and primed period whereas ydro-(60.1884), sulphuric acid-(52.0741), etha-(60.5150) and ascorbate priming (66.7733).